Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T17:25:36+01:00
A) (x-2)-(2-x)=x-2-2+x=2x-4
b) (a+b)+(2a-b)-(a-2b)=a+b+2a-b-a+2b=2a+2b
c) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1
d) -(2a²-3ab)-(2b-3a²)+(-ab-b)=-2a²+3ab-2b+3a²-ab-b=a²+2ab-3b
2010-02-17T17:27:19+01:00
A) (x-2)-(2-x)= x-2-2+x=2x-4
b)(a+b)+(2a-b)-(a-2b) = a+b+2a-b-a+2b= 2a+2b
c)(3x-y+1)-(x+y)+(y-x) =3x-y+z-x-y+y-x= x-y
d)-(2a²- 3ab)-(2b-3a²)+(-ab-b)= -2a²+3ab-2b+3a²-ab-b= a²+2ab-3b
1 5 1
2010-02-17T17:28:53+01:00
A)2x-x²+4+2x=4x+4+x²
b)a+b+2a-b-a+2b=2a+2b
c)3x-y+1-x-y+y-x=x-y+1
d)2a²- 3ab-2b+3a²-ab-b=5a²-4ab-3b